Recurrent desmoplastic small round cell tumor responding to an mTOR inhibitor containing regimen. Issue 1 (22nd September 2017) - Tarek, Nidale; Hayes‐Jordan, Andrea; Salvador, Laura; McAleer, Mary F.; Herzog, Cynthia E.; Huh, Winston W.
Abstract: Desmoplastic small round cell tumor (DSRCT) is a rare mesenchymal tumor that typically presents with multiple abdominal masses. Initial treatment is multimodal in nature. Patients with relapsed DSRCT have a poor prognosis, and there are no standard therapies. We report our experience with five patients treated with vinorelbine, cyclophosphamide, and temsirolimus (VCT). Median number of VCT courses delivered was 7 (range 4–14 courses), and partial response was observed in all patients. Median time to progression or relapse was 8.5 months (range 7–16 months). Neutropenia and mucositis were most common toxicities (n = 4 each).